Effects of dietary vegetable oil on atlantic salmon hepatocyte fatty acid desaturation and liver fatty acid compositions - Tocher, Douglas R; Bell, J Gordon; Dick, James R; Crampton, Viv (Lipids, 2003)
Fatty acyl desaturase activities, involved in the conversion of the C18 EFA, 18:2n-6 and 18:3n-3, to the highly unsaturated fatty acids (HUFA) 20:4n-6, 20:5n-3 and 22:6n-3, are known to be under nutritional regulation. Specifically, the activity of the desaturation/elongation pathway is depressed when animals, including fish, are fed fish oils rich in n-3HUFA compared to animals fed vegetable oils rich in C18 EFA. The primary aims of the present study were a) to establish the relative importance of product inhibition (n-3HUFA) versus increased substrate concentration (C18 EFA) and, b) to determine whether 18:2n-6 and 18:3n-3 differ in their effects, on the hepatic fatty acyl desaturation/elongation pathway in Atlantic salmon (Salmo salar). Smolts were fed ten experimental diets containing blends of two vegetable oils, linseed (LO) and rapeseed oil (RO), and fish oil (FO) in a triangular mixture design for 50 weeks. Fish were sampled after 32 and 50 weeks, lipid and fatty acid composition of liver determined, fatty acyl desaturation/elongation activity estimated in hepatocytes using [1-14C]18:3n-3 as substrate, and the data subjected to regression analyses. Dietary 18:2n-6 was positively correlated, and n-3HUFA negatively correlated, with lipid content of liver. Dietary 20:5n-3 and 22:6n-3 were positively correlated with liver fatty acids with a slope greater than unity suggesting relative retention and deposition of these HUFA. In contrast, dietary 18:2n-6 and 18:3n-3 were positively correlated with liver fatty acids with a slope of less than unity suggesting metabolism via β-oxidation and/or desaturation/elongation. Consistent with this, fatty acyl desaturation/elongation in hepatocytes was significantly increased by feeding diets containing vegetable oils. Dietary 20:5n-3 and 22:6n-3 levels were negatively correlated with hepatocyte fatty acyl desaturation. At 32 weeks, 18:2n-6 but not 18:3n-3, was positively correlated with hepatocyte fatty acyl desaturation activity whereas the reverse was true at 50 weeks. ...